2020
DOI: 10.1101/2020.03.18.994004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying cardiac actinin interactomes reveals sarcomere crosstalk with RNA-binding proteins

Abstract: 1 Actinins are actin cross-linkers that are expressed in nearly all cells and harbor mutations in 2 heritable diseases. We deployed proximity-dependent biotinylation to identify actinin proximity 3 proteins and RNA transcripts in human cardiomyocytes to reveal new functions of the actin 4 cytoskeleton. We identified 285 proximity protein partners including unexpected effectors of 5 RNA-binding and metabolism, and interrogated dynamic partners using a sarcomere assembly 6 model. Mammalian two-hybrid studies est… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…A deeper analysis of proteomic data revealed that the protein levels of ACTN2, several other sarcomere-associated proteins and desmosomal proteins were markedly lower in ACTN2mut hiPSC-CMs ( Table S1 ). Some of these proteins (FLNC, MYOZ2, NEBL, SYNPO2, SYNPO2L, TTN) are known to interact directly with ACTN2 [ 22 , 23 , 24 ]. On the other hand, FHL1 and FHL2, located at the Z-disk of the sarcomere [ 25 , 26 ] were more abundant in ACTN2mut.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A deeper analysis of proteomic data revealed that the protein levels of ACTN2, several other sarcomere-associated proteins and desmosomal proteins were markedly lower in ACTN2mut hiPSC-CMs ( Table S1 ). Some of these proteins (FLNC, MYOZ2, NEBL, SYNPO2, SYNPO2L, TTN) are known to interact directly with ACTN2 [ 22 , 23 , 24 ]. On the other hand, FHL1 and FHL2, located at the Z-disk of the sarcomere [ 25 , 26 ] were more abundant in ACTN2mut.…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with the low abundance of several sarcomeric proteins, including ACTN2 in ACTN2mut hiPSC-CMs, leading to a poorly developed sarcomere and possibly to a more immature cardiomyocyte state. In addition, SYNPO2 and SYNPO2L, which contribute to early assembly and stabilization of the Z-disk via interaction with filamin and ACTN2 [ 22 , 27 ], were also less abundant, supporting disruption of the ACTN2 interactome and deficient sarcomere development in ACTN2mut hiPSC-CMs. The reduced Z-disk integration of exogenous MUT-ACTN2 in ACTN2wt by live cell imaging supports the susceptibility of mutant ACTN2 to aggregate.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the mutations may alter the very sensitive interplay between the components of the sarcomere and/or protein dynamics and thereby induce contractile dysfunction (for review, see [4]). Furthermore, interactions of sarcomeric proteins with associated proteins might be altered, affecting signaling and thereby protein transcription, metabolism, inflammation, oxidation, cell death, protein degradation, fibrosis, cell-cell communication, Ca 2þ homeostasis, and so on [95][96][97].…”
Section: Sarcomeric Dysfunctionmentioning
confidence: 99%
“…Global inactivation of alpha-actinin two in mice is not compatible with life, but a cardiac specific mosaic inactivation suggests a crucial role of the protein for cardimyocyte maturation via serum response factor signaling (Guo et al, 2021). Moreover, a role of alpha-actinin two in regulating cardiac mitochondrial function has been proposed recently (Zech et al, 2022), in part by acting as a scaffold for mitochondrial messenger RNAs via binding to RNA-binding proteins (Ladha et al, 2020).…”
Section: Structure and Function Of Alpha-actininmentioning
confidence: 99%